1995
DOI: 10.1107/s010827019400363x
|View full text |Cite
|
Sign up to set email alerts
|

Hexafluorophosphate Salts of Cyclopentadienyliron(II) Complexes of Dibenzodioxin and 1-Methyldibenzodioxin

Abstract: both complexes, O--C bonds of the coordinated ring are shorter than those of the uncoordinated ring. CommentThe title complexes were synthesized, following a previously described procedure (Sutherland, Pi6rko, Gill & Lee, 1982), by the reaction of catechol with (r/6-1,2 -dichlorobenzene)(r/5-Cp)iron(II) hexafluorophosphate and with (r/6-2,3-dichlorotoluene)(r/5-Cp)iron(II) hexafluorophosphate to give (1) and (2), respectively. Crystals of both complexes were grown from acetone-Michloromethane-diethyl ether sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
2
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
4
2
0
Order By: Relevance
“…The C-O distances, however, are quite different, as the bond extending from the bridging O atom to the C atom of the coordinated ring is significantly shorter than the C-O bond extending towards the uncoordinated ring [1.361 5and 1.393 (5) Å , respectively]. Both these observations agree with earlier findings for phenoxathiin and azaphenoxathiin complexes (Lynch et al, 1986;Sutherland et al, 1988) and for dibenzodioxin complexes (Pió rko et al, , 1995Hendsbee et al, 2010).…”
Section: Commentsupporting
confidence: 88%
See 1 more Smart Citation
“…The C-O distances, however, are quite different, as the bond extending from the bridging O atom to the C atom of the coordinated ring is significantly shorter than the C-O bond extending towards the uncoordinated ring [1.361 5and 1.393 (5) Å , respectively]. Both these observations agree with earlier findings for phenoxathiin and azaphenoxathiin complexes (Lynch et al, 1986;Sutherland et al, 1988) and for dibenzodioxin complexes (Pió rko et al, , 1995Hendsbee et al, 2010).…”
Section: Commentsupporting
confidence: 88%
“…The earlier studies of the synthesis and structure of dibenzodioxin and thianthrene FeCp complexes suggested that only FeCp-in-fold molecules are formed in such a reaction. This conclusion was based on the results of several crystallographic studies (Simonsen et al, 1985;Abboud et al, 1990;Christie et al, 1994;Pió rko et al, 1994Pió rko et al, , 1995. Recently, we reported that a double nucleophilic substitution reaction leading to the formation of (1,2,3,4,4a,10a-)-1-methylthian-threne FeCp hexafluoridophosphate gave rise to a mixture of both in-fold and out-of-fold isomers, as found in a crystallographic study of the reaction products (Hendsbee et al, 2009).…”
Section: Commentmentioning
confidence: 61%
“…The distances from the Fe ion to the Cp plane and to the complexed benzene ring plane are 1.666 (3) and 1.537 (3) Å , respectively, in molecule A, 1.662 (3) and 1.551 (3) Å in B, and 1.648 (4)/1.538 (3) and 1.701 (4)/1.538 (3) Å in the two disorder components of the Cp ring in C. These values are close to those reported in the literature for similar complexes (see, for example, Lynch et al, 1986;Abboud et al, 1990;Pió rko et al, 1995;Fuentealba et al, 2007;Manzur et al, 2007;Jenkins et al, 2008).…”
Section: Commentsupporting
confidence: 87%
“…The complexed Cp and benzene rings of (I) are nearly coplanar in all three molecules, with a dihedral angle of 0.2 (5) for molecule A, 2.8 (5) for B, and 2.19 (4) and 6.86 (6) for the disordered Cp ring in C. These values are in the range observed for other thianthrene and dibenzodioxin FeCp complexes in our previous studies (see, for example, Simonsen et al, 1985;Lynch et al, 1986;Abboud et al, 1990Abboud et al, , 1991Christie et al, 1994;Pió rko et al, 1995). The Cp-Febenzene ring centroid vectors are nearly collinear, with angles of 179.65 (8) and 178.42 (7) for molecules A and B, and 178.69 (7) and 176.39 (7) for the disordered Cp ring in C. These values are typically found in the literature for FeCparene complexes (see, for example, Manzur et al, 2000;Fuentealba et al, 2007).…”
Section: Commentsupporting
confidence: 72%
See 1 more Smart Citation